2018
DOI: 10.1126/sciadv.aao3820
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic electromagnetic knot in a three-dimensional skyrmion

Abstract: We experimentally simulate a quantum-mechanical particle interacting with knotted electromagnetic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 38 publications
(58 reference statements)
2
52
0
Order By: Relevance
“…Néel and Bloch textures, in any ferroic material. This structure resembles vortex rings previously described in the context of topological semimetals 28 , superfluids 29 and quantum chromodynamics 30 , and three-dimensional skyrmions and solitons that have been predicted and observed in ultra-cold gases (that is, Bose-Einstein condensates) 31,32 . Such a three-dimensional structure deviates from the ordinary two-dimensional skyrmions observed in magnetic systems.…”
Section: Letter Researchsupporting
confidence: 76%
“…Néel and Bloch textures, in any ferroic material. This structure resembles vortex rings previously described in the context of topological semimetals 28 , superfluids 29 and quantum chromodynamics 30 , and three-dimensional skyrmions and solitons that have been predicted and observed in ultra-cold gases (that is, Bose-Einstein condensates) 31,32 . Such a three-dimensional structure deviates from the ordinary two-dimensional skyrmions observed in magnetic systems.…”
Section: Letter Researchsupporting
confidence: 76%
“…At present, the theory considering electromagnetic fields with a different topology, known as «knotted electromagnetic fields» (KEMF), is developed; corresponding practical studies were reported [14][15][16][17] . These fields have a certain practical relevance, as they can be used in the industry of efficient new generation communication systems.…”
mentioning
confidence: 99%
“…3e) to initiate the creation process experimentally with a condensate initially prepared in | m = 1〉, where | m 〉 denotes the m th spinor component. Such techniques 32,33 have been used to prepare, e.g., non-singular 25,27,34 and multiply quantised vortices 29 , as well as monopoles 35 , skyrmions 36 , and knots 37 .…”
Section: Resultsmentioning
confidence: 99%